An Evaluation of the Efficiency of the Gulf Cooperation Council's Centralized Procedure by the Gulf Regulatory Authorities and Pharmaceutical Companies: Recommendations for an Improved Model. (July 2015) - Al-Rubaie, Mohamed H.; Salek, Sam; Walker, Stuart
The aim of this study was to examine the views and experiences of the Gulf Cooperation Council (GCC) states and pharmaceutical companies to identify the strengths and weaknesses of the GCC centralized registration procedure (GCC-CP). Results of a questionnaire designed for the study and completed by GCC regulatory authorities and pharmaceutical companies who registered products through the GCC-CP showed that it is an effective system. However, it demonstrated that there is room for improvement. For example, provision of clear guidelines, transparency of procedures, effective interactions between authorities and companies, an increase in the number of committee meetings, and the use of electronic online submissions would shorten approval times and enhance the quality of review practice as well as encourage pharmaceutical companies to use the GCC-CP system. This research enabled the development of an improved model of the GCC-CP to be proposed to the GCC Health Authorities, which could expedite patients' access to medicines in the region.